Pengaruh Sekolah Lapang Organik Terhadap Pengetahuan Dan Minat Petani Dalam Bertani Organik Di Kecamatan Tanara - Mustopa, Ahmad Jazilil (Sharia Agribusiness Journal, 2024)
ABSTRACTApart from providing safe and healthy food, organic farming also has a conservation function because cultivation is environmentally friendly.Organic farming is currently one of the programs promoted by the Ministry of Agriculture through the Pro Organic Farmers Movement (Genta Organik).Genta Organic's derivative program is an organic farming thematic field school, one of which is implemented by the Tanara Agricultural Extension Center.This research tries to analyze the extent of the influence of field school activities on farmers' knowledge and interest in organic farming.Using 50 participants as research respondents, and a pre-experimental design method with one group pretest-posttest presented with descriptive quantitative analysis and hypothesis testing using inferential statistics.This research produces a significant influence from organic field schools on farmers' knowledge and interest in organic farming.Keywords: organic farming; field school; knowledge; interests ABSTRAKPertanian organik selain sebagai pemenuhan pangan yang aman dan sehat juga memiliki fungsi pelestarian karena budidaya yang ramah lingkungan. Pertanian organik saat ini menjadi salah satu program yang diusung Kementerian Pertanian lewat Gerakan Tani Pro Organik (Genta Organik). Bentuk program turunan Genta Organik adalah sekolah lapang tematik pertanian organik yang salah satunya dilaksanakan oleh Balai Penyuluhan Pertanian Tanara. Penelitian ini mencoba menganalisis sejauh mana pengaruh kegiatan sekolah lapang terhadap pengetahuan dan minat petani dalam bertani organik. Menggunakan 50 peserta sebagai responden penelitian, dan metode pre-experimental design dengan one group pretest-posttest disajikan dengan analisis kuantitatif deskriptif. Penelitian ini menghasilkan pengaruh yang signifikan dari sekolah lapang organik terhadap pengetahuan dan minat petani dalam bertani organik.Kata Kunci: pertanian organik; sekolah lapang; pengetahuan; minat